Expression of NF-L protein in the sensorimotor cortex during the modeling of transient ischemia against the background of sensitization by brain antigen and immunocorrection of the changes - L. M. Yaremenko; A. N. Grabovoy; L.P. Bidna; S. Ye. Shepelev; M. M. Grusha (Patologìâ)
Abstract